Dross has spoken. A group of YouTuber DrossRotzank’s Peruvian fans’ routines and ritual - Félix, Diana (2019)
This research aims to understand the routine practices and use of audiovisual content from the venezuelan youtuber DrossRotzank by members of his fan club in Lima, Perú. Therefore, the main objective is to analyse why the peruvian fans like to see the content produced by DrossRotzank. To solve this question, digital ethnography was used to analyze publications in social networks, chat rooms, images, videos, and six interviews with outstanding fans who narrated their preferences for the horror genre and paranormal or strange situations that appear in the audiovisual content. Among the findings we learned the fans share the cult for the contents of the youtuber, through a digital social world composed by several social networks and digital platforms where the participants converge. This study analyzes the reasons why the fans have formed a community where they maintain shared taste for the youtuber, and the routines and rituales they put into practice to make use of the YouTube channel of DrossRotzank, due to their taste for entertainment they find in the audiovisual content and the direct interaction with the youtuber through social networks.